Installation of Religious Moderation in The Society 5.0 Era to Prevent Radicalism in Early Children in Kindergarten, Pangkah District - Ratnawati, Siti; Irmawati; Nur’Afita, Luthfatul Laeli; Marpuah, Dr. (Universitas Nahdlatul Ulama Surabaya, 2023)
The symptoms of radicalism continue to grow not only in adolescents and adults but also in early childhood.The polemic of early childhood radicalization can also be seen in kindergartens. Radicalism can be preventedby implementing religious moderation from an early age. This study aims to analyze the cultivation ofreligious moderation in early childhood to prevent radicalism. The research method used is quantitativedescriptive research. This research was conducted in kindergarten institutions in the Pangkah sub-district,Tegal Regency, Central Java. The subject of this research used 25 kindergartens in the slot deposit 5000 Pangkah sub-districtconsisting of 1018 students. Data collection techniques used observation, interviews, and documentation.The analysis technique was a descriptive qualitative analysis of the cultivation of religious moderationin early childhood to prevent radicalism. The results showed an increase in the cultivation of religiousmoderation is the cultivation of religious moderation in all kindergartens in the Pangkah Subdistrict,emphasizes cognitive elements that strongly support the cultivation of religious moderation throughBloom’s Taxonomy theory, which is instilled through the attitude of understanding of global diversity,ideals of homeland, tolerance, and anti-violence in schools in the era of society 5.0. Culturing religiousmoderation to prevent radicalism in early childhood in Pangkah District Kindergarten was successfullycarried out with an average success indicator of 89.83%. This research contributes to supporting thegovernment, especially the Ministry of Education, in implementing the independent curriculum and theP5 project.